Education on Recognizing of Rice Bug Pest (Leptocorisa acuta F.) and its Control on Rice Plant in Palakahembi Village, East Sumba Regency - Sri Ita Traigan (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
The Palakahembi Village is one of the villages whose main commodity is rice plants. The present community-service activities were implemented in Palakahembi Village, East Sumba Regency, East Nusa Tenggara Province. This activity targeted the farmer groups of Ndula Kita and Marangga Panamung. It aimed to provide the farmers with knowledge about pest control and how to control the rice bugs with biopesticide and fitfall trap. The activities we carried out included workshops and mentoring practices for making fitfall trap, making biopesticide, and application of biopesticide on rice in the field. The farmers were provided with knowledge about pest control by making them conduct a direct survey of rice plants that were attacked in the field, followed by the practice of making fitfall trap and making biopesticide and their application to rice plants. The results showed that the farmers were able to understand the morphology and the symptoms of the rice bug attack, as well as the techniques of making the biopesticide along with the application of the biopesticide in the rice plant. Besides, the application of biopesticide at a concentration of 1/5 L (1 litre of biopesticide/5 litres of water) in rice plants also resulted in lower attack rates as much as 80% and higher productivity (6,2 tons/ha) compared to the control group.